TLR adaptor protein MYD88 mediates sensitivity to HDAC inhibitors via a cytokine-dependent mechanism - New, M; Sheikh, S; Bekheet, M; Olzscha, H; Thezenas, M; Care, M; Fotheringham, S; Tooze, R; Kessler, B; La Thangue, N (American Association for Cancer Research, 2016)
Histone deacetylase (HDAC) inhibitors have proven useful therapeutic agents for certain haematological cancers. However, HDAC inhibition causes diverse cellular outcomes, and identification of cancer-relevant pathways within these outcomes remains unresolved. In this study, we utilized an unbiased loss-of-function screen and identified the Toll-like receptor (TLR) adaptor protein MYD88 as a key regulator of the anti-proliferative effects of HDAC inhibition. High expression of MYD88 exhibited increased sensitivity to HDAC inhibitors; conversely, low expression coincided with reduced sensitivity. MYD88-dependent TLR signalling controlled cytokine levels, which then acted via an extracellular mechanism to maintain cell proliferation and sensitize cells to HDAC inhibition. MYD88 activity was directly regulated through lysine acetylation and was deacetylated by HDAC6. MYD88 was a component of a wider acetylation signature in the ABC subgroup of DLBCL, and one of the most frequent mutations in MYD88, L265P, conferred increased cell sensitivity to HDAC inhibitors. Our study defines acetylation of MYD88 which, by regulating TLR-dependent signalling to cytokine genes, influences the anti-proliferative effects of HDAC inhibitors. Our results provide a possible explanation for the sensitivity of malignancies of haematological origin to HDAC inhibitor-based therapy.